Laser and forming technology - an idea and the way of implementation - Geiger, Manfred; Merklein, Marion; Pitz, Matthias (Journal of Materials Processing Technology, 2004)
This paper will give a survey of some of the actual research activities at the Chair of Manufacturing Technology in Erlangen concerning laser and forming technology. In detail the paper will deal with two main focuses of development: laser forming of aluminum alloys and laser-assisted forming of high strength steels. Laser forming is a technology often used for small series productions and for adjustment of small electronic components. In contrast to laser forming, which is a forming technology that is common for over 20 years, laser-assisted forming is an example of a new production technology that is able to enhance the forming limits of high strength steels. © 2004 Elsevier B.V. All rights reserved.
LFT Import::2019-07-16 (1028)
Keywords: Laser forming; Laser-assisted forming; Mechanical properties; Microstructure